Odpowiedzi

2010-03-01T18:27:49+01:00
A]
0=(x-1)-(3x-5)
x-1-3x+5=0
-4x=-4
x=1

b]
(-½x+1)+³/₂x=3
-0,5x+1,5x=3-1
x=2

c]
3(1-x)-(1-2x)=9
3-3x-1+2x=9
-x=9-3+1
-x=7
x=-7
2010-03-01T18:29:52+01:00
A)0=(x-1) - (3x - 5)
0=x+1-3x+5
-x+3x=5+1
2x=6 /:2
x=3

b)(-½x + 1) +³x/₂=3
- 0,5x+ 1,5=3-1
x=2

c)3(1-x) - (1 - 2x) =9
3-3x-1+2x=9
-3x+2x=9-3+1
-x=7
x=-7
2010-03-01T20:58:45+01:00
Rozwiąż równianie :) daje najlepszą :D
a)0=(x-1) - (3x - 5)
0=x-1-3x+5
3x-x=4
2x=4
x=4:2
x=2

b)(-½x + 1) +³x/₂=3
³x/₂ ??? naprawdę nie mogę się domyślec co to?
może?
-½x + 1 +³/₂x=3
-½x+³/₂x=3-1
x=2

c)3(1-x) - (1 - 2x) =9
3-3x-1+2x=9
-3x+2x=9+1-3
-x=7
x=-7